Study on Adult Chinchilla (Chinchilla lanigera) Preferences for Cages of Different Sizes - Zsolt Szendrő; Stanisław Łapiński; Zsolt Matics; Zsolt Gerencsér (Animals)
The study aimed to investigate adult chinchillas’ preferences when choosing between cages with different floor areas, heights, or both. The size of the cages with a larger floor area was double that of the standard-sized cages in the farms (0.25 and 0.50 m2), while their height was 2.4 times that of the standard-sized cages (0.4 and 1 m). The chinchillas (10–14 in each cohort) were housed in blocks of cages where they could move freely between the smaller and larger cages. The chinchillas’ location preferences were monitored continuously over five days using infrared video recording. The chinchillas were observed in the cages with smaller floor areas 1.9 and 2.7 times more frequently than in the larger ones (p < 0.001) during the dark (active) and light (resting) periods of the day, respectively. When the cage height was 0.4 m, they chose it 3.4 and 6.7 times more frequently, respectively, than the cage that was 1 m high (p < 0.001). When both the floor size and the height were increased, the chinchillas still favored the smaller and lower cages (p < 0.001). The study findings suggest that adult chinchillas show a preference for smaller and shorter cages when the small and large cages are not environment enrichment barren, especially during the rest period of the day, even when the floor area, height, or both are increased. In the future, it would be important to investigate different forms of cage enrichment.